MANIFESTATION OF SOCIAL ANXIETY IN PUTU WIJAYA'S SHORT STORY, MALU - Br. Sembiring, Elita Modesta; Matondang, Saiful Anwar; Manugeren, M. (Penerbit Lafadz Jaya, 2026)
This study examines the manifestation of social anxiety in Putu Wijaya’s short story Malu through a literary psychological perspective. Social anxiety is understood as a socially constructed emotional condition shaped by fear of judgment, shame, and social expectations. Using a qualitative descriptive approach, this research analyzes the psychological states, behavioral responses, and narrative techniques presented in the text. The primary data source is the short story Malu, while secondary sources include scholarly works on psychological criticism, social anxiety, and Indonesian literature. The analysis reveals that social anxiety in Malu is manifested through internal psychological tension, including excessive self-awareness, fear of negative evaluation, and feelings of shame (Malu). These psychological conditions influence the protagonist’s behavior, leading to avoidance, silence, and emotional restraint in social interactions. Additionally, Putu Wijaya employs narrative techniques such as internal monologue, repetition, and absurd situations to effectively represent the protagonist’s emotional struggle and highlight the oppressive nature of social norms. The findings suggest that social anxiety in Malu functions as a mechanism of social control, reinforcing conformity and limiting individual agency. Rather than portraying anxiety as a purely personal disorder, the short story emphasizes its cultural and social dimensions within Indonesian society. This study contributes to literary theory and criticism by demonstrating how psychological analysis can deepen the understanding of emotional representation in Indonesian literary works. It also encourages further interdisciplinary research on the relationship between literature, psychology, and culture.